A Bibliography of Jonathan Swift’s Works and Reception in Hungary - Hartvig, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The present bibliography of translations, adaptations and imitations, together with critical articles and chapters, is an attempt to document the presence of Jonathan Swift in Hungary. Complete translations, poetry and shorter writings, adaptations of mainly the first two voyages of Gulliver ’s Travels, and creative re-writings are arranged in chronological order. Critical articles, notices and chapters on Swift follow in alphabetical order. Editions of the best known Hungarian Gulliveriads, Frigyes Karinthy’s Faremidó and Capillária, and Sándor Szathmári’s Kazohinia, are listed separately, but also in chronological sequence, within the section “Creative Imitations.” The English translation of the titles of items written in Hungarian is provided in brackets.